ECO-COSMOPOLITANISM, CULTURAL HYBRIDITY, AND INDIGENOUS AGENCY IN INDONESIAN CHILDREN LITERACY TEXTBOOK - Fatikhatur Rizqya; Aulia Noor Eliza; Aulia Rahma Rahmadani (Four Son Scholarship, 2026)
This study examines the children’s literacy textbook Nona Bupu: Pemandu Cilik dari Lereng Gunung Inerie through the lens of postcolonial ecocriticism and cultural hybridity. Traditional children’s literature from postcolonial regions frequently succumbs to a dual trap: either romanticizing the Indigenous subject as a static, pre-modern artifact or framing the regional landscape purely through the tourist gaze. This article investigates how the narrative subverts these paradigms by positioning its young protagonist, Nona Bupu, not merely as a passive cultural guide but as an active agent of eco-cosmopolitanism. By analyzing the intersection of sacred local geography (Gunung Inerie), traditional socio-religious practices (ka sa’o and meghe), and intercultural encounters with domestic tourists, the study demonstrates how the text fosters a nuanced space of cultural hybridity. The methodology employs a qualitative textual and ideological analysis rooted in postcolonial and ecocritical frameworks. The findings reveal that the text actively deconstructs the colonial binary of the civilized metropolitan observer versus the regional subject. Instead, it offers a contemporary model of indigenous agency where local ecological wisdom and global modernity coexist dialogically, establishing a vital precedent for progressive, decolonial pedagogical materials in primary education